Missense mutation in selenocysteine synthase causes cardio-respiratory failure and perinatal death in mice which can be compensated by selenium-independent GPX4 - Noelia Fradejas-Villar (Elsevier, 2021)
Selenoproteins are a small family of proteins containing the trace element selenium in form of the rare amino acid selenocysteine (Sec), which is decoded by the UGA codon. In humans, a number of pathogenic variants in genes encoding distinct selenoproteins or selenoprotein biosynthesis factors have been identified. Pathogenic variants in selenocysteine synthase (SEPSECS), which catalyzes the last step in Sec-tRNA[Ser]Sec biosynthesis, were reported in children suffering from progressive cerebello-cerebral atrophy. To understand the pathomechanism associated with SEPSECS deficiency, we generated a novel mouse model recapitulating the respective human pathogenic p.Y334C variant in the murine Sepsecs gene (SepsecsY334C). Unlike in patients, pups homozygous for the p.Y334C variant died perinatally with signs of cardio-respiratory failure. Perinatal death is reminiscent of the Sedaghatian spondylometaphyseal dysplasia disorder in humans, which is caused by pathogenic variants in the gene encoding the selenoprotein and key ferroptosis regulator glutathione peroxidase 4 (GPX4). Protein expression levels of distinct selenoproteins in SepsecsY334C/Y334C mice were found to be generally reduced in brain and isolated cortical neurons, while transcriptomics analysis uncovered an upregulation of NRF2-regulated genes. Crossbreeding of SepsecsY334C/Y334C mice with mice harboring a targeted mutation of the catalytically active Sec to Cys in GPX4 rescued perinatal death of SepsecsY334C/Y334C mice, showing that the cardio-respiratory defects of SepsecsY334C/Y334C mice were caused by the lack of GPX4. Like in SepsecsY334C/Y334C mice, selenoprotein expression levels remained low and NRF2-regulated genes remained highly expressed in these compound mutant mice, indicating that selenium-independent GPX4, along with a sustained antioxidant response are sufficient to compensate for dysfunctional Sec-tRNA[Ser]Sec biosynthesis. Our findings imply that children with pathogenic variants in SEPSECS or GPX4 may even benefit from treatments that incompletely compensate for impaired GPX4 activity.